2021
DOI: 10.1192/bjb.2021.102
|View full text |Cite
|
Sign up to set email alerts
|

The ethics and management of cannabis use in pregnancy following decriminalisation and licensing for medical use: narrative review

Abstract: Aims and method As drug policies pertaining to cannabis use become more liberalised, the prevalence of cannabis use in pregnancy could increase. However, there is limited guidance available for clinicians. This paper presents a narrative review of literature published in the past 16 years (2006–2021) to (a) address the impact of legalisation and decriminalisation on the risks, ethics and support of women who use cannabis during pregnancy and (b) develop guidance for clinicians. Results B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…The study highlighted increased cannabis use trends and unmitigated risks in pregnancy. However, the lack of specific guidance for clinicians and the need for more research may limit the practical application of the study's findings [5]. In the realm of medical education, Ting, et al embarked on a scoping review to explore the evidence-guided approach to portfolio-guided teaching and assessing effectiveness.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study highlighted increased cannabis use trends and unmitigated risks in pregnancy. However, the lack of specific guidance for clinicians and the need for more research may limit the practical application of the study's findings [5]. In the realm of medical education, Ting, et al embarked on a scoping review to explore the evidence-guided approach to portfolio-guided teaching and assessing effectiveness.…”
Section: Study Selectionmentioning
confidence: 99%
“…In essence, this systematic review aspires to contribute valuable insights to practitioners, policymakers, and scholars engaged in the ongoing discourse on medical ethics [5]. By unraveling the layers of ethical complexity in modern healthcare, we aim to foster a deeper understanding of the ethical imperatives that guide medical decision-making, ultimately promoting a more informed and ethically robust approach to contemporary medical practices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical data on the impact of CBD use during pregnancy and breastfeeding are lacking [19]. National institutions advise against its use in these circumstances [20][21][22]. Another concern regards the true quantity of cannabinoids in CBD-based products [23].…”
Section: Introductionmentioning
confidence: 99%
“…The legalization of cannabis across 33 states in the United States and other countries has increased cannabis use and changed perceptions toward this practice. 1 A study using data from the National Survey on Drug Use and Health indicated that from 2005 to 2012, the number of individuals who used cannabis and believed cannabis use to be safe during pregnancy increased from 25.8% to 65.4%. 2 Data from the 2017 Pregnancy Risk Assessment Monitoring System (PRAMS) showed that 9.8% of women self-reported cannabis use before pregnancy, 4.2% during pregnancy, and 5.5% after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis use during the perinatal period is of concern because early prenatal exposure to cannabis can affect the development of the endocannabinoid system which can impact the development of executive function and regulation of the emotional system and cognition in the offspring. 1 Gestational cannabis exposure has been associated with decreased time in a quiet sleep state, tremors, a decrease in the early cognitive performance of infants, as well as adverse effects on sustained attention and short-term memory. 5 Furthermore, it is known that the psychoactive component of cannabis, delta-9-tetrahydrocannabinol, transfers into breast milk, which may impact postnatal brain development.…”
Section: Introductionmentioning
confidence: 99%